Comparative Analysis of Serum IgE and Eosinophil Levels in Patients with Asthma and Allergic Conjunctivitis - Khan, Mohammed Asaduzzaman; Islam, Mohammad Shafiqul; Islam, Mohammad Shafiqul; Akter, Farhana; Shahen, Md (Journal of Dhaka National Medical College & Hospital, 2026)
Background: Asthma and allergic conjunctivitis are closely related to allergic disorders driven by IgE-mediated and eosinophil-associated inflammation. Both conditions share common immunological pathways involving Th2 cytokines and hypersensitivity to environmental allergens. Measuring serum IgE and eosinophil levels provides valuable insight into the severity and type of allergic response. Comparative evaluation of these biomarkers helps to clarify their relationship and diagnostic significance in asthma and allergic conjunctivitis patients. Objectives: This study aimed to compare serum IgE and eosinophil levels between asthma and allergic conjunctivitis patients, and correlate these biomarkers with clinical parameters. Method and Materials: This prospective study included 134 adults with asthma or AC. Data on demographics and clinical history were collected via questionnaire. Serum IgE (ELISA) and eosinophil counts (automated analyzer) were measured. Statistical analysis used independent t-tests and chi-squaretests to compare the groups, with p<0.05 considered significant. Ethical approval was obtained. Result: The study included 134 participants (mean age 34.8±10.6years; 53.7% male). Asthma patients (53.7%) showed significantly higher mean serum IgE (512.3±146.7 vs 438.5±122.4 IU/mL, p=0.021) and eosinophil counts (468.7±132.9 vs 392.4±118.6cells/μL, p=0.017) than allergic conjunctivitis patients. A strong positive correlation existed between IgE and eosinophils (r=0.62, p<0.001). Longer disease duration and a positive family history (64.9%) were associated with elevated IgE. Conclusion: Asthma patients exhibited significantly higher serum IgE and eosinophil levels than those with allergic conjunctivitis, with a strong correlation between these biomarkers. J Dhaka National Med. Coll. Hos. 2025; 31 (02): 34-39